Breaking A Playfair Cipher Using Single and Multipoints Crossover Based on Heuristic Algorithms - Naji M.A.; Atee H.A.; Jebur R.S.; Hammood D.A.; Der C.S.; Abosinnee A.S.; Yasari A.K.I.; Ahmad R.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cryptography; Heuristic algorithms; Heuristic methods; MATLAB; Breakings; Crossover rates; Cryptanalyze; Heuristics algorithm; Key search; Memetic algorithms; Multi-points; Playfair; Playfair ciphers; Single point; Genetic algorithms